PENGEMBANGAN MEDIA PEMBELAJARAN HAFALAN AL-QUR'AN BERBASIS ANIMASI INTERAKTIF UNTUK ANAK SEKOLAH DASAR - Adhityarini, Esthi (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
The purpose of this research is to apply learning media in the form of interactive, innovative and interesting animated learning applications that can be used for primary school children's learning in making it easier for children to memorize short letters of the Qur'an. This study uses a system development method starting from software requirements analysis, design, code generation, testing to the implementation stage. After going through all the processes that end with testing and implementation, this interactive animation of learning to memorize the Qur'an can be used as an alternative media for children to memorize easily and interestingly. in children; non-formal learning media for children using interactive animations can increase children's enthusiasm for learning, especially in memorizing the Qur'an; using interactive animation.